Volume changes of thalamus, hippocampus and cerebellum are associated with specific CSF profile in MS. (April 2022) - Bajrami, Albulena; Magliozzi, Roberta; Pisani, Anna I; Pizzini, Francesca B; Crescenzo, Francesco; Marastoni, Damiano; Calabrese, Massimiliano
Background: The underlying pathogenesis of surface-in grey matter abnormalities in MS, demonstrated by both neuropathology and advanced MRI analyses, is under investigation and it might be related to CSF-mediated mechanism of inflammation and/or damage. Objective: To examine the link of CSF inflammatory profile with the damage of three regions early-involved in MS and bordering with CSF: thalamus, hippocampus and cerebellum. Methods: In this longitudinal, prospective study, we evaluated, in 109 relapsing–remitting MS patients, at diagnosis and after 2-year follow-up, the association between the baseline CSF level of 19 inflammatory mediators and the volume changes of thalamus, hippocampus, cerebellar cortex and control regions (globus pallidus, putamen). Results: The multivariable analysis showed that the CXCL13 and sCD163 CSF levels at baseline were independent predictors of thalamus (R model 2 = 0 . 80 ; p < 0.001) and hippocampus (R model 2 = 0 . 47 ; p < 0.001) volume change after 2-year follow-up. These molecules, plus CCL25, IFN-γ and fibrinogen, were independent predictors of the cerebellar cortex volume loss (R model 2 = 0 . 60 ; p < 0.001). No independent predictors of volume changes of the control regions were found. Conclusion: Our results indicate an association between the CSF inflammatory profile and grey matter volume loss of regions anatomically close to CSF boundaries, thus supporting the hypothesis of a surface-in GM damage in MS.